Realization of the Constitutional Idea of Balance of Public and Private Interests in the Context of the Provisions of the Draft New Code of Criminal Procedure of the RA - Ghazinyan, G. (Bulletin of Yerevan University C: Jurisprudence, 2020)
The enshrinement of the principle of proportionality in domestic law and its practical application by the constitutional courts and courts of general jurisdiction, as a procedure for ensuring respect for human rights by the state - is typical for both of the countries of common and continental law. This principle is reflected in the domestic legislation at the level of the RA Constitution, and the specific regulations aimed at balancing public and private interests have been included in the criminal procedural regulations. The article highlights the existing theoretical approaches to the principle of proportionality, international legal requirements, in the light of which the relevant solutions of the Draft new Code of Criminal Procedure of the RA Criminal Procedure Code were analyzed.